Nuclear medicine : practical physics, artifacts, and pitfalls - Pryma, Daniel A. ([New York] : Oxford University Press, 2015)
A readable explanation of the physics behind radiobiology, radiation detection, and molecular imaging with gamma and PET cameras. Case-based scenarios illustrate common artifacts and pitfalls, and a concluding chapter provides 20 annotated questions and answers.
Previously issued in print: 2014.
Includes index.
Specialized.
Description based on online resource; title from home page (viewed on May 23, 2016).
Keywords: Nuclear medicine